Pemanfaatan Jenis Tumbuhan Sebagai Obat di Desa Bandar setia Kecamatan Percut Sei Tuan - Sari, Ayu Indah; Susilo, Ferdinand; Nasution, Jamilah; Riyanto, Riyanto (Universitas Medan Area, 2024)
Medical plants are defined as types of plants where some or all parts of the plants are used as medicine which is believed to cure a disease. This study aims to determine the types of plants that have the potential as medicine and their use by the people of Bandar Setia Village, Percut Sei Tuan District. This type of research is descriptive qualitative and quantitative research. Data analysis in this study used descriptive analysis techniques. The results showed that there are 46 plant species that have the potential as medicine in Bandar Setia Village which are grouped into 25 families. Parts of plants that are used include leaves 42%, fruit 27%, rhizome 15%, roots 4%, flowers 4%, seeds 4% and tubers 4%. Obtaining plants that have the potential to be used as medicine in Bandar Setia Village by wild 47%. Plant processing method by boiling 28,26%. Use of plants as medicine 56,52%, health 43,47%.